Demanda por gasto público no Brasil no período pós-redemocratizaç\~ao: Testes da lei de Wagner e da hipótese de mill de ilus\~ao fiscal - Alexandre Manoe Angelo da Silva; Rozane Bezerra Siqueira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– This paper examines whether fiscal illusion can help to explain the behavior of federal government expenditures in Brazil during period 1990-2011. The analyses is based on a median voter model that admits that the degree of tax visibility may affect the individual's perception of his tax burden and, thus, may influences his demand for public expenditure. We find evidence that the higher the proportion of the (more visible) income tax in the total tax revenue raised by the federal government, the lower the federal government's spending, which supports the hypothesis that there is fiscal illusion in the demand for federal government expenditure. Besides, this study also confirmed the Wagner's Law in the long run.
Keywords: H11; H30; H50; 330; fiscal illusion; public expenditure; Wagner's law; Fiskalillusion; Öffentliche Ausgaben; Wagnersches Gesetz; Brasilien